2003
DOI: 10.1590/s0104-14282003000200011
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos históricos da vulcanização

Abstract: As borrachas, para serem convertidas em materiais úteis do ponto de vista de aplicações, precisam ser misturadas a alguns ingredientes, os quais vão lhes dar as características desejadas para, então, serem vulcanizadas. Neste artigo, os aspectos históricos da vulcanização são abordados bem como a evolução dos aditivos essenciais à maioria das formulações.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 19 publications
0
11
0
12
Order By: Relevance
“…Através da vulcanização consegue-se transformar as propriedades plás-ticas da borracha, eliminar sua sensibilidade ao calor e obter um corpo elástico capaz de retomar suas dimensões primitivas depois de uma deformação, mesmo em condições extremas de temperatura [8][9][10][11][12] .…”
Section: Materiaisunclassified
“…Através da vulcanização consegue-se transformar as propriedades plás-ticas da borracha, eliminar sua sensibilidade ao calor e obter um corpo elástico capaz de retomar suas dimensões primitivas depois de uma deformação, mesmo em condições extremas de temperatura [8][9][10][11][12] .…”
Section: Materiaisunclassified
“…It is a natural, biocompatible and flexible polymer obtained mainly from the Hevea brasiliensis tree. In general, rubbers are benefited by vulcanization processes which consist of the crosslink of the polymer chains improving mainly the mechanical properties of the compound [8,9] . Currently, the rubber has been of great interest of study as result of the possibility of composites preparation as a new approach to technology development [10,11] which may contain organic compounds such Defatted Soy Flour [12] , or carbon black [13,14] as both reinforce and conductive agents.…”
Section: Introductionmentioning
confidence: 99%
“…However, this cost could be reduced using silica obtained from organic waste. A Similar study recently reported in the literature describes methods for obtaining silica from rice hull ash (residue production) [15][16][17] , oilshare residue [18] , and the use of organoclay as a substituent of silica (fillers) in rubber composites [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to various type of fiber, it can be seen that the tensile strength is affected by filler type, filler size, filler shape and their surface area [7]. It would also be controlled by the nature of the filler and matrix [8]. By comparing four natural fibers in this study, we may proved that pineapple fiber showed the highest tensile strength among others, although with low filler loading (5%) compared to other.…”
Section: Tensile Strengthmentioning
confidence: 69%